PELUANG PENDIDIKAN DAN HUBUNGAN ANTARETNIK: PERSPEKTIF PENDIDIKAN KRITIS - Dadang Supradan (Sosio-Didaktika: Social Science Education Journal, 2014)
This article was written to provide an overview of the opportunities of education and inter-ethnic relations in the perspective of critical education. The author conducted in-depth study of literature, especia lly in relation to critical education perspective on inter-ethnic relations and educational opportunities. Thoughts on the critical education of modernism to the postmodernism marks optimism into the role of education as cultural tr ansformation and production area, not as reproduction of culture. Meanwhile, inter-ethnic relations deepens national integration, among other things: (1) promote community life in harmony, (2) realizing cultural relatio nship model, (3) appreciating the differences, (4) repairing the emergence of social prejudices, (5) valuing diversity and foster democracy. In this context, the school holds a very important role as a venue for the empowerment and liberation of individuals and groups in a just society by promoting individual and collective autonomy in participatory democratic system that respects the diversity and plurality of social and cultural groups. Democracy as a celebration of difference and diversity, not to serve the agenda of the elite minority and the majority of the ruling ideology.